The Effect of Profitability and Leverage on Tax Avoidance with Company Size as a Moderating Variable - Afuan Fajrian Putra; Dava Prayoga Nurcahya; Annisa Fidanta Shafir; Reny Lia Riantika (Proceeding International Conference on Accounting and Finance, 2025)
The coal mining industry is one of the resources that has a large contribution to state revenues every year. Despite its large contribution, this industry is also one of the sectors indicated to be carrying out tax avoidance. Tax Avoidance practices have been influenced by several factors. One of the factors believed to influence tax avoidance practices in a company is the level of profitability and leverage. Then this study uses a moderating variable in the form of company size which is different from previous studies. The object of this study is the financial statements of coal mining companies listed on the Indonesia Stock Exchange where the data collection method uses the purposive sampling method, where the number of samples obtained is 70 samples from 16 coal mining companies listed on the Indonesia Stock Exchange in 2019-2023. This study uses IBM SPSS Statistic Software version 29 to conduct several tests such as classical assumption tests, regression tests, f tests, determination coefficient tests. The results of this study indicate that profitability has a positive effect on tax avoidance, while leverage does not have a positive effect on tax avoidance. Company size is able to moderate the effect of profitability on tax avoidance, but company size is not able to moderate leverage on tax avoidance.